Lumbar Sympathetic Plexus Block as a Treatment for Postamputation Pain: Methodology for a Randomized Controlled Trial. Issue 12 (8th March 2018) - McCormick, Zachary L; Hendrix, Andrew; Dayanim, David; Clay, Bryan; Kirsling, Amy; Harden, Norman
Abstract: Objective: We present a technical protocol for rigorous assessment of patient-reported outcomes and psychophysical testing relevant to lumbar sympathetic blocks for the treatment of postamputation pain (PAP). This description is intended to inform future prospective investigation. Design: Series of four participants from a blinded randomized sham-controlled trial. Setting: Tertiary, urban, academic pain medicine center. Subjects: Four participants with a single lower limb amputation and associated chronic PAP. Methods: Participants were randomized to receive a lumbar sympathetic block with 0.25% bupivacaine or sham needle placement. Patient-rated outcome measures included the numerical rating scale (NRS) for pain, the McGill Pain Questionnaire–Short Form, Center for Epidemiological Studies Depression Scale, Pain and Anxiety Symptoms Scale–short version, and Pain Disability Index (PDI). Psychophysical and biometric testing was also performed, which included vibration sensation testing, pinprick sensation testing, brush sensation testing, Von Frey repeated weighted pinprick sensation, and thermal quantitative sensory testing. Results: In the four described cases, treatment of PAP with a single lumbar sympathetic block but not sham intervention resulted in reduction of both residual limb pain and phantom limb pain as well as perceived disability on the PDI at three-month follow-up. Conclusions: An appropriately powered randomized controlled study using this methodology may not only aid in determining the possible clinical efficacy of lumbar sympathetic block in PAP, but could also improve our understanding of underlying pathophysiologic mechanisms of PAP.